Development Of Tcr-like Single Domain Antibody By Incorporating Immunoglobulin Isotypes For Latent Tuberculosis Diagnostics And Therapeutics Application Against Heat Shock Protein 16 Kda Peptide Presented By Hla-a2 - Liu, Hua Qiang (2024)
Heat shock protein 16 kDa (HSP 16 kDa) is essential for the survival of latent Mycobacterium tuberculosis. Therefore, a peptide-MHC presentation of HSP 16 kDa could be a potential diagnostic and therapeutic target for latent tuberculosis (LTB). This study aimed to generate different immunoglobulin isotype pairings on a TCR-like single-domain antibody (sDAb) and subsequently investigate its diagnostic and therapeutic potential in LTB, utilizing a model cell presenting the target peptide. A previously generated TCR-like sDAb that can bind to HSP 16 kDa was first fused to a human IgG1, IgG2, IgG4, IgA, IgD, IgE, and IgM Fc-receptor via a linker. The fusion product, sDAb-Fc, was expressed in HEK293-F cells and subsequently purified. Its diagnostic potential was investigated via cell-based ELISA utilizing MCF-7 cells peptide-pulsed with HSP 16 kDa peptides. Antibody-dependent cell-mediated cytotoxicity (ADCC) of MCF-7 cells was also conducted to investigate its therapeutic potential. Finally, TCR-like sDAb-IgG1, IgG2, and IgG4 were successfully produced transiently in HEK293 F cells and purified using protein A chromatography.